Probabilistic optimization of fatigue maintenance for welded components in steel bridges based on LEFM and LCCM - Zeng, Yong (Array, 2018)
In this paper a probabilistic-based method for fatigue maintenance optimization of steel bridge’s welded joints, combined with linear elastic fracture mechanics (LEFM), the structure reliability, and life cycle cost method(LCCM) is proposed. The probabilistic analysis method can be used with the fatigue maintenance of steel bridges. Weld cracks are classified by its size and maintenance decisions, and are made according to its size classification. Maintenance cost is divided into inspection, repair and failure costs, according to the life cycle cost method. The maintenance optimization strategy is transformed to minimize the expected lifetime total costs with the constraints of the minimum acceptable reliability index to attain the most cost-optimal inspection and repair for the balanced costs between risk and safety. An example concerning the transverse stiffeners of welded components in the main girder of suspension bridge is investigated through the research of some parameters sensitivity. Among all the parameters, the inspection cost is the most remarkable. The optimal time interval of repair will delay based on the increase of the inspection cost. The optimal time interval of repair will advance based on the increase of repair cost. A discount rate can drastically change the value of the total cost, but when the probability of failure is very small, the increase of failure cost has little effect on the optimal time interval of repair. The method presented in this paper can be conducted using the similar maintenance of steel structures.